Thermal Analysis of System in Package Considering Boundary Conditions for Long-Term Reliability Studies - Djallel Eddine Touati; Aziz Oukaira; Ahmad Hassan; Mohamed Ali; Yvon Savaria; Ahmed Lakhssassi (IEEE Access)
This paper proposes an integrated Foster-based thermal network for a System in Package (SiP) that models thermal interaction between package layers to predict the transient temperature of junctions and interlayer compression in SiP. The critical factors contributing to impedance mismatch are detailed to ensure modeling accuracy. Important factors include the boundary conditions and the interface layer of the thermal material. With the help of the Finite Element Method (FEM) and data curve fitting, thermal parameters are derived and expressed as a function of boundary conditions. The proposed modeling method is demonstrated with 3D heterogeneous System in Package models implemented in Simulink for long-term temperature predictions. Predicted junction and interlayer temperatures show good accuracy, confirmed by reported results obtained by Finite Element Analysis (FEA). The importance of considering the boundary conditions and the materials used in the various interfaces is shown through simulation results. Neglecting one of these key factors, the predicted temperature differs by as much as 14.5 °C in the reported results. The proposed thermal network is consistent with FEA, while computing much faster and producing results that differ by no more than 0.5 °C, unlike previously reported models.